2018
DOI: 10.1016/j.addbeh.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Measuring perceptions related to e-cigarettes: Important principles and next steps to enhance study validity

Abstract: Measuring perceptions associated with e-cigarette use can provide valuable information to help explain why youth and adults initiate and continue to use e-cigarettes. However, given the complexity of e-cigarette devices and their continuing evolution, measures of perceptions of this product have varied greatly. Our goal, as members of the working group on e-cigarette measurement within the Tobacco Centers of Regulatory Science (TCORS) network, is to provide guidance to researchers developing surveys concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 66 publications
(116 reference statements)
0
48
0
Order By: Relevance
“…E-cigarette use is a complex behavior, and response options in questionnaires assessing perceptions and reasons in general may not be representative for all users, cigarette smokers, dual users, and non-users. Our overview, in addition to the work of Gibson et al [ 26 ] and Pearson et al [ 24 ], validated measures such as the Fagerström test for nicotine dependence [ 104 ] and the International Tobacco Control measures [ 105 ], and adds insight into developing and validating items for measuring e-cigarette use, risk perceptions of e-cigarettes, perceived benefits of e-cigarettes, and reasons for e-cigarette use. Summarizing, validated measures provide insight into e-cigarette use to develop tailored information based on the needs of e-cigarette users, cigarette smokers, dual users, and non-users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-cigarette use is a complex behavior, and response options in questionnaires assessing perceptions and reasons in general may not be representative for all users, cigarette smokers, dual users, and non-users. Our overview, in addition to the work of Gibson et al [ 26 ] and Pearson et al [ 24 ], validated measures such as the Fagerström test for nicotine dependence [ 104 ] and the International Tobacco Control measures [ 105 ], and adds insight into developing and validating items for measuring e-cigarette use, risk perceptions of e-cigarettes, perceived benefits of e-cigarettes, and reasons for e-cigarette use. Summarizing, validated measures provide insight into e-cigarette use to develop tailored information based on the needs of e-cigarette users, cigarette smokers, dual users, and non-users.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the appeal of e-cigarettes is increasing among non-users, it is interesting to study the reasons non-users report that could lead them to initiate e-cigarette use, and whether these reasons differ from cigarette smokers switching to e-cigarettes. In order to better understand the process of switching from cigarettes to e-cigarettes or experimenting with e-cigarettes, it is important to have an insight into perceptions of e-cigarettes and reasons for use among different types of users [ 6 , 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. This paper therefore provides an overview of such perceptions and reasons among adult and youth e-cigarette users, cigarette smokers, dual users, and non-users.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Little is known about how the overall risk perception of e-cigarettes has evolved or changed over time. In addition, previous studies 20 used different approaches to measure risk perception of e-cigarettes, making findings difficult to compare across studies and over time. In the present study, we examine whether and to what extent the perceived relative harm of e-cigarettes compared with cigarettes has changed during a 6-year period (2012-2017) in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…ENDS and tobacco control policies at the local level may also shape risk perceptions, which were not controlled for in the present study. As one study suggested, harm perceptions can be evaluated using different measures (e.g., harm perception versus socio-norm perceptions); a future study with more comprehensive measures is needed [ 40 ]. In addition, we did not evaluate addiction perceptions in this study, which will be evaluated in a follow-up study.…”
Section: Discussionmentioning
confidence: 99%